DIGITALISASI UMKM DAN LITERASI KEUANGAN UNTUK KEBERLANJUTAN UMKM DI KABUPATEN CILACAP - Jayanti, Esih; Karnowati, Nandang Bekti (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the businesses that strongly support economic activity, especially in the conditions of the world economic crisis due to the COVID-19 pandemic. The increase in MSMEs shows how this sector is still a mainstay for the community economy. However, in the midst of this pandemic, almost all MSMEs were affected, and some became sluggish, including MSMEs in Cilacap Regency. Therefore, efforts are needed to overcome the affected MSMEs, so that MSMEs can run their business sustainably during the pandemic and post-pandemic periods later. The purpose of this study was to examine and analyze the effect of digitizing MSMEs and financial literacy on the sustainability of MSMEs in Cilacap Regency. The benefits of research for MSMEs can develop their business in a sustainable manner by paying attention to aspects of MSME digitization and financial literacy for MSMEs. This research method is a survey with interview techniques or direct questionnaires to MSMEs owners. By purposive sampling technique, the respondents in this study were MSMEs registered at the Integrated Business Service Center (PLUT) in Cilacap Regency. Data analysis used Multiple Linear Regression. The results showed that both partially and simultaneously the digitization of MSMEs and Financial Literacy had an effect on the Sustainability of MSMEs in Cilacap Regency.